FINANCIAL LITERACY, FINTECH ADOPTION, AND INVESTMENT DECISIONS: THE MEDIATING ROLE OF FINANCIAL INCLUSION AMONG BALI’S YOUNG GENERATION - Kusuma, Made Cahyadi Wiranata (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study investigates the influence of financial literacy and financial technology (FinTech) on investment decisions among Generation Z in Bali Province, with financial inclusion as a mediating variable. The issue arises from the rapid adoption of FinTech amid persistently low financial literacy and limited access to inclusive financial services in Indonesia. The research questions whether financial literacy and FinTech adoption affect investment decisions directly or indirectly through financial inclusion. The novelty of this study lies in integrating three key variables—financial literacy, FinTech adoption, and financial inclusion—into a single empirical model to explain actual investment behavior. Prior research often examines these factors separately and lacks focus on youth in regional areas. This research applies a quantitative method using a cross-sectional design. Data were collected from 100 respondents aged 17–26 using purposive sampling. The analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS 4.0. The results show that financial literacy has a direct effect on investment decisions, but not on financial inclusion. FinTech adoption significantly influences both financial inclusion and investment decisions. Furthermore, financial inclusion partially mediates the effect of FinTech adoption on investment behavior. The study concludes that digital access through FinTech plays a vital role in encouraging youth investment. The findings suggest that financial education should be supported by inclusive financial infrastructure to improve decision-making among young digital users.